The Professionalisation of Personal Financial Planning in Malaysia - The Practitioner's Perspectives - Tan, Geoffrey Hoe Kock (2003)
The financial planning profession in Malaysia is in a curious regulatory posture. While the financial services industry is one of the most highly regulated sectors in the country, the financial planning profession itself lacks a stand-alone regulatory system. Currently, financial planners are not regulated and the financial planning industry itself is straddling between two regulators – the Securities Commission and Bank Negara. This study found that the lack of a social security system in Malaysia to protect the public from social and economic distress has driven home the urgent need and necessity for prudent financial planning and for individuals to arrange their financial affairs to meet their life goals and objectives. Contributions and savings via the Employees Provident Fund and the Socso are simply not enough to insure a comfortable living after one’s retirement or support to dependents arising from the income earner’s premature death or disability. As Malaysians live longer, they need additional resources to finance the extra years of life after retirement. The financial planning industry in Malaysia is said to be about 20 years behind that of the United States where it started. This study found that if the right regulatory framework is nurtured and the profession itself work on developing what are the core competencies that the financial planner should focus on in order to offer quality advice to the client, and uphold the high ethical standards expected, then this emerging profession in Malaysia can leapfrog the usual stumbling advances and catch up with the other developed countries. The successful financial planner is a qualified professional who has the necessary training, experience and competencies, and is fully committed to deliver quality advice and services to his or her client. Financial planning is a multi-discipline profession and one that can only be practised by qualified professionals as it affects the financial state of affairs of the client.